1982
DOI: 10.1128/mcb.2.12.1558
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Sensitive Chinese Hamster Fibroblast Mutant with a Defect in RNA Metabolism

Abstract: We describe a new temperature-sensitive mutant of Chinese hamster cell fibroblasts. After a shift to the nonpermissive temperature of 40.5°C, the rates of DNA, RNA, and protein synthesis declined rapidly (to n50% within 12 h) and the progression of unsynchronized cells through the cell cycle was affected. We believe that DNA synthesis came to a halt after a short time, because cells no longer entered the S phase. The decrease in protein synthesis at 40.5°C was shown to be a consequence of a decrease in the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1989
1989

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The message was on authentic ribosomes as defined by their sensitivity to puromycin. In addition, the large amount of fiber mRNA migrating in the 80S region of the gradient appeared to be associated with ribosomes, since pronase treatment at 4°C (which disrupts ribonucleoprotein aggregates but not monosomes [25,59,68]) did not alter the distribution of the fiber mRNA (data not shown). Moreover, Anderson and Klessig (5) demonstrated that these ribosomes had initiated translation in vivo and were active in translational runoff in vitro.…”
Section: Resultsmentioning
confidence: 96%
“…The message was on authentic ribosomes as defined by their sensitivity to puromycin. In addition, the large amount of fiber mRNA migrating in the 80S region of the gradient appeared to be associated with ribosomes, since pronase treatment at 4°C (which disrupts ribonucleoprotein aggregates but not monosomes [25,59,68]) did not alter the distribution of the fiber mRNA (data not shown). Moreover, Anderson and Klessig (5) demonstrated that these ribosomes had initiated translation in vivo and were active in translational runoff in vitro.…”
Section: Resultsmentioning
confidence: 96%
“…It was renamed H3, and H3.5 is a subclone of H 3 . The temperaturesensitive mutant H20 with a defect in RNA metabolism was subsequently isolated from WglA cells by ethyl methane sulfonate mutagenesis (Wong and Schemer, 1982). These cells were routinely maintained in Dulbec-CO'S modified Eagle's medium (DMEM) containing 10% cadet calf serum.…”
Section: Materials and Methods Cell Lines And Culture Conditionsmentioning
confidence: 99%